Studies on South-east Asian fireflies: Abscondita, a new genus with details of life history, flashing patterns and behaviour of Abs. chinensis (L.) and Abs. terminalis (Olivier) (Coleoptera: Lampyridae: Luciolinae) - Ballantyne, Lesley; Fu, Xinhua; Lambkin, Christine; Jeng, Ming-Luen; Faust, Lynn; Wijekoon, W. M. C. D.; Li, Daiqin; Zhu, Tengfui (Zootaxa, 2013)
Abscondita, a new genus of fireflies from South-east Asia, is described from males and females of Abs. anceyi (Olivier 1883), Abs. cerata (Olivier 1911), Abs. chinensis (L. 1767), Abs. perplexa (Walker 1858), Abs. promelaena (Walker 1858) and Abs. terminalis (Olivier 1883), all transferred from Luciola Laporte. Both L. dubia Olivier 1903 and L. dejeani Gemminger 1870 are synonymised with Luciola perplexa (Walker), and L. aegrota Olivier 1891 and L. melaspis Bourgeois 1909 with L. promelaena Walker. Females are characterised by their bursa plates. Larvae are associated and described for Abs. anceyi (Olivier), Abs. chinensis (L.) and Abs. terminalis (Olivier). Taxonomic issues regarding the identification of species with very similar colouration of pale dorsum and black tipped elytra are addressed and in some cases resolved. A neotype for Luciola chinensis (L.) is erected and Luciola praeusta (Kiesenwetter 1874) is synonymised with L. chinensis (L.). Descriptions of life histories, biology and flashing patterns of populations of Abs. chinensis and Abs. terminalis from central China are included. Abs. terminalis is the first Asian firefly known to possess multiple flash trains where males are documented to display with repeating flash trains.